Human Capital and Earnings of Female Immigrants to Australia, Canada, and the United States - Heather Antecol; Deborah A. Cobb-Clark; Stephen J. Trejo (Institute for the Study of Labor (IZA), 2002)
Census data for 1990/91 indicate that Australian and Canadian female immigrants have higher levels of English fluency, education (relative to native-born women), and income (relative to native-born women) than do U.S. female immigrants. A prominent explanation for this skill deficit of U.S. immigrant women is that the United States receives a much larger share of immigrants from Latin America than do the other two countries. Similar to previous findings for male immigrants, the apparent skill disadvantage of foreign-born women in the United States (relative to foreign-born women in Australia and Canada) shrinks dramatically once we exclude immigrants originating in Latin America. In all three countries, men are much more likely than women to gain admission on the basis of immigration criteria related to labor market considerations rather than family relationships. For this reason, we might expect that the stronger emphasis on skill-based admissions in Australia and Canada compared to the United States would have a larger impact on cross-country differences in the skill content of male rather than female immigration flows. Therefore, our findings of similar patterns for men and women and of the key role played by national origin both suggest that factors other than immigration policy per se are important contributors to the observed skill differences between immigrants to these three destination countries.
Keywords: J31; J68; J61; 330; immigration; female immigrants; human capital; Frauenerwerbstätigkeit; Migranten; Qualifikation; Humankapital; Frauenarbeitslohn; Australien; Kanada; Vereinigte Staaten